(3MGTjI GdYdGeI eMeO GdNVQj Ydj GdehdO GdTQja deMeO GdgGOjs - (3eMeO Hf eUWaj Hf MSf GdTGaYj GdOejGWj GdNVQj,J (B1287 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi JfRg Yf GdhGdO hGdehdhO s
(3BNQgG (B:s
(3hde jLYd aj jhe hdGOJg ef GdJcGdja eG LYdg aj jhe GdLeYg hPdc dRjGOI EcQGeg Udj Gddg Ydjg hSde hGddg SHMGfg hJYGdj CYde HGdUhGH s
(3HbjI GdebOeI JUhjQgG ZjQ hGVMs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B100 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B281s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B150 s
Keywords: (3GdJGQjNs